Tradisi Pisuke Pada Perkawinan Adat Masyarakat Lombok Perspektif Hukum Islam - Nuril Habibi; Lia Astari (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
pisuke. This study aims to find out or analyze how the pisuke tradition in traditional marriages of Lombok people in Ranggagata Village, Praya Barat Daya District, Central Lombok Regency, Islamic Law perspective. This research uses qualitative methods and qualitative descriptive design. Data collection was carried out using field observation techniques, interviews, and documentation. Data analysis techniques used include data collection, data presentation, and data verification. Analysis of research data, the results of the research are as follows: 1) Pisuke tradition processes, starting to involve village heads and local traditional leaders as representatives of both parties to discuss the number of pisuke that will be distributed by the male side for the female side, in determining the number of pisuke there are certain categories that support the high or low number of pisuke, namely the education level of women and the economic level of men but things This is not absolute as a reference because it goes back to the deliberative decision of both parties in determining the number of pisuke. 2) Pisuke is a custom or habit that is carried out for generations. Pisuke is one of the customs used for the settlement of Lombok customary nikhan, although pisuke is not contained in Islamic law but pisuke has become a tradition that is considered good to be applied among the community because it does not violate nash or syara If it is related to living, in this case pisuke has no relationship at all with living because there are several points that make it cannot be equated with living, That is the gift of pisuke which is sometimes given after the contract and before the contract